Restricted Interests and Autism: Further Assessment of Preferences for a Variety of Leisure Items. Issue 1 (January 2018) - Spear, Monica A.; Karsten, Amanda; White, Emily A.
Researchers have yet to identify the conditions under which people diagnosed with autism spectrum disorder demonstrate restricted interests; it is possible that the impression of restricted interests is strengthened when a limited variety of items are included in a client's preference assessments. This study will extend past research on preferences of children with autism by (a) examining participants' preferences for unreplenished (familiar) play or leisure items versus items that are replenished frequently, (b) assessing if participants who prefer replenished items select items with properties that are matched or unmatched to their most preferred unreplenished item, and (c) assessing if participants who show an exclusive preference for unreplenished items will select replenished items during response-restriction and enhanced-replenished pool manipulations. Participants were four adolescents with autism and a caregiver-reported history of restricted interests. One participant selected both unreplenished (familiar) items and replenished (novel) items without further manipulations. The remaining three participants only selected replenished-matched leisure items after additional manipulations. Results are discussed in terms of the ethical and practical importance of assessing a range of potential reinforcers, particularly with clients who demonstrate restricted interests.